PERAN LAYANAN KONSELING INDIVIDU DENGAN MEDIA ART THERAPHY UNTUK MENGURANGI PERILAKU PEOPLE PLEASER PADA SISWA KELAS X-7 SMA NEGERI 1 COLOMADU TAHUN 2026 - Jati Pratiwi, Fitria; Heru Sri Suryanti, Hera; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fitria Jati Pratiwi.THE ROLE OF INDIVIDUAL COUNSELING SERVICES WITH ART THERAPY MEDIA TO REDUCE PEOPLE PLEASER BEHAVIOR IN CLASS X-7 STUDENTS OF SMA NEGERI 1 COLOMADU IN 2026. The purpose of this study was to determine the role of individual counseling services with art therapy media in reducing people-pleaser behavior in class X-7 students at SMA Negeri 1 Colomadu.People-pleaser behavior is a tendency to have difficulty saying no, prioritizing the needs of others over oneself, fearing rejection, and this behavior can lead to overthinking and suppressing feelings due to fear of expressing emotions. The research method used is Descriptive Qualitative. The subject of this study was 1 student from class X-7. The data technique used follows Miles and Huberman, with stages of data collection, data reduction, data presentation, and drawing conclusions. Data collection techniques used interviews, observation, and documentation. This research was conducted at SMA Negeri 1 Colomadu.According to the results of the research conducted, art therapy media can help students reduce people-pleaser behavior, where students can express their feelings and emotions through drawings, can refuse requests from others, and can prioritize their own needs. Based on the results of the study on the role of individual counseling with art therapy media to reduce people-pleaser behavior in class X-7 students of SMA Negeri 1 Colomadu in the 2026 academic year, it can be concluded that individual counseling services with art therapy media can help reduce people-pleaser behavior in students.